Estudo de degradação anaeróbia do 2,4D em reator anaeróbio horizontal de leito fixo (RAHLF) inoculado com microrganismos enriquecidos provenientes do sedimento do reservatório de Itaipú-PR - Damasceno, Bianca Gouvea (2023)
Pesticides act with the purpose of increasing agricultural production at levels proportional to the demand for food, which has grown exponentially in recent decades due to the increase in world population. Due to the toxic potential of these products and their use in huge doses, they have become a recurrent source of contamination in the environmental matrices in the country. In order to recover the affected environments and minimize the impacts from these pollutants, the development of efficient processes for the treatment in the eradication of these elements from the environment is the target of research. The main objective of this work was to evaluate the performance of the horizontal anaerobic fixed bed bioreactor (RAHLF) in the degradation of the herbicide 2,4 dichlorophenoxyacetic acid (2,4D), one of the most used pesticides in the world today, under anaerobic conditions and at methanogenic oxidation level. The validation of the results was done through the detection of 2,4D and intermediates by high performance liquid chromatography (HPLC) and confirmed its potential. The reactor was inoculated with sediment from the Itaipu reservoir, previously enriched under methanogenic conditions in the presence of 2,4D at a concentration of 1mg/L, during 376 days, with weekly monitoring of the consumption of organic matter via spectrometry, reaching in the 89th day of incubation removal of approximately 97% of COD. The accentuated and constant decay of COD strongly confirmed the presence of active and efficient biological activity, making necessary the feeding of carbon sources (0.01 mg/L of Sodium Lactate and 0.01 mg/L of Potassium Acetate), periodically of the medium. After the inoculation, the reactor was operated with a TDH of 88hours for 60 days, reaching stability from the 27th day of operation with a reasonable average of 63% of removal efficiency, having had its best performance on the 38th day with approximately 96.52%, leaving the initial concentration of 0.59 mg/L and reaching 0.02 mg/L of 2,4D. It was proven efficient removal of 2,4D in all samples collected during the RAHLF operation, in the order between 14.79 to 96.52%. Also, on the 34th day, the complete transformation of 2,4D was recognized, since all the intermediates of 2,4D belonging to the anaerobic degradation route adopted in this study were detected in trace concentrations, with 0.385 mg/L of 2,4D; 0.103 mg/L of 2,4DCP; 0.130 mg/L of 4CP and 0.052 mg/L of phenol in the effluent sample.